Determinants of the use of nonpharmacological analgesia for labor pain management: a national population-based study. Issue 11 (November 2020) - Merrer, Jade; Chantry, Anne A.; Khoshnood, Babak; Blondel, Béatrice; Le Ray, Camille; Bonnet, Marie-Pierre
Abstract : Abstract: Besides neuraxial analgesia, nonpharmacological methods are also proposed to help women coping with pain during labor. We aimed to identify the individual and organizational factors associated with the use of nonpharmacological analgesia for labor pain management. Women who attempted vaginal delivery with labor analgesia were selected among participants included in the 2016 National Perinatal Survey, a population-based cross-sectional study. Labor analgesia was studied as neuraxial analgesia alone, nonpharmacological analgesia alone, and neuraxial and nonpharmacological analgesia combined. The associations were studied using multilevel multinomial logistic regression. Among the 9231 women included, 62.4% had neuraxial analgesia alone, 6.4% had nonpharmacological analgesia alone, and 31.2% had both. Nonpharmacological analgesia alone or combined with neuraxial analgesia were both associated with high educational level (adjusted odds ratio 1.55; 95% confidence interval [CI], 1.08-2.23 and 1.39; 95% CI, 1.18-1.63), antenatal preference to deliver without neuraxial analgesia, and public maternity unit status. Nonpharmacological analgesia alone was more frequent among multiparous women, and in maternity units with an anesthesiologist not dedicated to delivery unit (1.57; 95% CI, 1.16-2.12) and with the lowest midwife workload (2.15; 95% CI, 1.43-3.22). Neuraxial and nonpharmacological analgesia combined was negatively associated with inadequate prenatal care (0.70; 95% CI, 0.53-0.94). In France, most women who had nonpharmacological analgesia during labor used it as a complementary method to neuraxial analgesia. The use of nonpharmacological analgesia combined with neuraxial analgesia mainly depends on the woman's preference, but also on socioeconomic factors, quality of prenatal care, and care organization. Abstract : Supplemental Digital Content is Available in the Text.In France, nonpharmacological analgesia is mostly combined with neuraxial analgesia and depends on antenatal preference, socioeconomic factors, quality of care, and care organization.